Improved (Photo)catalytic Propene Hydration in a Gas/Solid System by Using Heteropolyacid/Oxide Composites: Electron Paramagnetic Resonance, Acidity, and Role of Water. Issue 13 (3rd April 2017) - García‐López, Elisa I.; Marcì, Giuseppe; Pomilla, Francesca R.; Liotta, Leonarda F.; Megna, Bartolomeo; Paganini, Maria C.; Gionco, Chiara; Giamello, Elio; Palmisano, Leonardo
Abstract : Binary materials composed of the oxides SiO2, TiO2 and N‐doped TiO2 and the Keggin heteropolyacid (PW12 ) were prepared and physicochemically characterized. They were used as catalysts and photocatalysts for the hydration of propene to 2‐propanol. The characterization of the samples, particularly the electron paramagnetic resonance (EPR) spectroscopy results and the acidity properties, were useful to explain the key role played by the PW12 in the composite materials in the thermal and photoassisted catalytic processes. The simultaneous presence of heat and UV light improved the activity of PW12 in the thermal process, and the binary materials showed better (photo)catalytic activities than that of the bare PW12 in almost all cases. For the first time, this work evidenced through EPR spectroscopy that the increase of reactivity under irradiation could be attributed to the ability of photoexcited PW12 to trap electrons, particularly if the PW12 is supported. Moreover, the effect of water on the reactivity was also studied. Abstract : Binary materials composed of the oxides SiO2, TiO2 and N‐doped TiO2 and the Keggin heteropolyacid (PW12 ) are prepared and characterized. The materials are used as catalysts and photocatalysts for the hydration of propene to 2‐propanol.